2021
DOI: 10.1038/s41467-021-24087-8
|View full text |Cite
|
Sign up to set email alerts
|

Vpr counteracts the restriction of LAPTM5 to promote HIV-1 infection in macrophages

Abstract: The HIV-1 accessory proteins Vif, Vpu, and Nef can promote infection by overcoming the inhibitory effects of the host cell restriction factors APOBEC3G, Tetherin, and SERINC5, respectively. However, how the HIV-1 accessory protein Vpr enhances infection in macrophages but not in CD4+ T cells remains elusive. Here, we report that Vpr counteracts lysosomal-associated transmembrane protein 5 (LAPTM5), a potent inhibitor of HIV-1 particle infectivity, to enhance HIV-1 infection in macrophages. LAPTM5 transports HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The CD4 + T cells were stimulated by adding CD3/CD28 activator magnetic beads (Invitrogen) to the culture medium for 2 d with 50 U/mL interleukin (IL)-2 (Biomol). The isolation and culturing of monocytes, MDMs, and MDDCs were performed ( 28 , 29 ). MDMs were generated by stimulating monocytes with 10 ng/mL recombinant human granulocyte-macrophage colony-stimulating factor (GM-CSF; R&D) and 50 ng/mL recombinant human macrophage colony-stimulating factor (M-CSF; R&D) for 7 d. MDDCs were generated by incubating CD14-purified monocytes in IMDM medium (Gibco) supplemented with 10% FBS, 2 mM l -glutamine, 100 IU/mL penicillin, 100 mg/mL streptomycin, 10 mM Hepes, 1% nonessential amino acids, 1 mM sodium pyruvate, 10 ng/mL GM-CSF, and 50 ng/mL IL-4 (Miltenyi Biotec).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CD4 + T cells were stimulated by adding CD3/CD28 activator magnetic beads (Invitrogen) to the culture medium for 2 d with 50 U/mL interleukin (IL)-2 (Biomol). The isolation and culturing of monocytes, MDMs, and MDDCs were performed ( 28 , 29 ). MDMs were generated by stimulating monocytes with 10 ng/mL recombinant human granulocyte-macrophage colony-stimulating factor (GM-CSF; R&D) and 50 ng/mL recombinant human macrophage colony-stimulating factor (M-CSF; R&D) for 7 d. MDDCs were generated by incubating CD14-purified monocytes in IMDM medium (Gibco) supplemented with 10% FBS, 2 mM l -glutamine, 100 IU/mL penicillin, 100 mg/mL streptomycin, 10 mM Hepes, 1% nonessential amino acids, 1 mM sodium pyruvate, 10 ng/mL GM-CSF, and 50 ng/mL IL-4 (Miltenyi Biotec).…”
Section: Methodsmentioning
confidence: 99%
“…The shRNA-mediated silencing of NRP-1 (RHS4430-200289197 or RHS4430-200215106 targeting open reading frame; RHS4430-200222352 targeting 3′-UTR) or control (catalog no. RHS4346) was achieved by introducing a microRNA-adapted shRNA lentivirus into the THP-1 cells, MDMs, and MDDCs ( 28 , 29 ). In summary, the freshly isolated monocytes were treated with Vpx and transduced with an shRNA lentivirus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether LCDR can be developed as a predictive biomarker for cancer diagnosis and targeted cancer therapy will be an ultimate goal long to reach. Together with a recent report on LAPTM5 restriction of HIV infection in macrophages ( 18 ), the paradigm-shifting findings by Yang et al. provide an excellent example bridging a nuclear lncRNA to cytoplasmic control of lysosome integrity and metabolism for cell homeostasis and antipathogen defense, a next frontier for the lncRNA field.…”
mentioning
confidence: 89%
“…Similarly, as Vpr increases viral envelope protein (Env) levels in primary macrophages ( 3 ), Vpr has also been reported to promote HIV-1 infection in dendritic cells by enhancing Env levels ( 4 ). Recently, we have demonstrated that lysosomal-associated transmembrane protein 5 (LAPTM5) is responsible for the long-sought anti-HIV-1 host restriction factor in primary macrophages suppressed by Vpr ( 5 ). We also observed high LAPTM5 expression levels in monocyte-derived dendritic cells (MDDCs), prompting us to investigate the relationship between Vpr and LAPTM5 in MDDCs and explore whether Vpr also counteracts the restriction of LAPTM5 to promote HIV-1 infection in dendritic cells.…”
Section: Lettermentioning
confidence: 99%